Dietary Risk Factors Associated with Development of Gastric Cancer in Nepal: A Hospital-Based Case-Control Study - Sunil Kumar Shah; Dev Ram Sunuwar; Narendra Kumar Chaudhary; Pushpa Rai; Pranil Man Singh Pradhan; Narayan Subedi; Madhu Dixit Devkota (Gastroenterology Research and Practice)
Objectives. Gastric cancer (GC) is one of the most prevalent neoplasms and a leading cause of mortality globally. To our knowledge, its relationship with dietary factors is not adequately studied and understood in the Nepalese context. This study is aimed at exploring the relationship between the possible dietary risk factors responsible for gastric cancer in Nepal. Methods. A hospital-based matched case-control study was conducted in two specialized cancer hospitals in Nepal. A total of 237 participants (79 cases and 158 controls) were included in the study. Patients diagnosed within one year (incidence case) with histologically confirmed gastric cancer were taken as cases, and healthy visitors of gastric and nongastric cancer patients without past and present history or not a suspected information of gastric cancer were included as controls. A face-to-face interview was conducted using a semi-structured food frequency questionnaire. Backward stepwise conditional logistic regression was used to estimate the magnitude of the association between the independent variables and gastric cancer. Results were presented as the crude odds ratio (COR) and adjusted odds ratio (AOR) with 95% confidence intervals (CI). A P value < 0.05 was considered statistically significant. Results. In the adjusted multivariable conditional logistic regression model, an increased risk of gastric cancer was more likely to have higher odds among those respondents who had a high consumption of processed meat (AOR=3.99, 95% CI: 0.90-17.66), preferences of a high amount of fats/oil (AOR=4.64, 95% CI: 1.56-13.72), and preferences of high amounts of salts (AOR=4.18, 95% CI: 1.30-13.44). Conversely, those respondents who consumed higher amounts of fruits (AOR=0.21, 95% CI: 0.07-0.65) were seen to have lower odds of gastric cancer. Conclusions. Our study found an increased risk of gastric cancer with frequent consumption of red meat, processed meat, high preferences of salt, fats/oil, and condiments. Regular consumption of fruits had a protective effect against gastric cancer. Providing nutrition education, public awareness, and lifestyle modification are primary steps to promote the avoidance of risk factors and change unhealthy dietary habits to prevent gastric cancer in Nepal.